Blockade of CB1 receptors prevents retention of extinction but does not increase low pre-incubated conditioned fear in the fear incubation procedure - Pickens, Charles L.; Theberge, Florence R. (My University, 2014)
We recently developed a procedure to study fear incubation in which rats given 100 tone-shock pairings over 10 days show low fear 2 days after conditioned fear training and high fear after 30 days. Notably, fear 2 days after 10 sessions of fear conditioning is lower than fear seen 2 days after a single session of fear conditioning, suggesting that fear is suppressed. Here, we investigate the potential role of CB1 receptor activation by endocannabinoids in this fear suppression. We gave rats 10 days of fear conditioning and then gave systemic injections of the CB1 receptor antagonist SR141716 before a conditioned fear test conducted 2 days later under extinction conditions. A second test was conducted without any injections on the following day (3 days post-training) to examine fear extinction retention. SR141716 injections did not increase fear expression 2 days after extended fear conditioning or affect within-session extinction, but impaired retention of between-session fear extinction in the day 3 test. These data suggest that CB1 receptor activation is not suppressing fear soon after extended fear conditioning in the fear incubation task. The data also add to an existing literature on the effects of CB1 receptors in extinction of conditioned fear.
Keywords: Fear incubation; Fear conditioning; PTSD; CB1; Endocannabinoids; Rimonabant